Using Modern Technologies in Teaching English Speaking Skill - kizi, Saydaliyeva Mashkhura Anvarjon (Miasto Przyszłości, 2023)
This article provides the necessary information on the use of modern methods and techniques for the development of oral speech competence of pupils in English classes. The scientific paper discussed several worldwide scientists’ study in this field, as well as difficulties in the development of oral speaking competency in today’s pupils. Technology dramatically helps students’ skill to improve their language acquisition. Nowadays, it is normal practice to employ technology to acquire a second language as a need. A comprehensive discussion of the several technology-based speaking ability training strategies was held.